Pengembangan Sumber Daya Manusia di Puskesmas Kabupaten Langkat Kecamatan Salapian - Harahap, Farida Hanim; Siregar, Helmi Zahra; Selian, Liza Syintani Putri; Panjaitan, Umaimah Zahroh; Oktami, Rida; Lestari, Winda Sri; Gurning, Fitriani Pramita (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The World Health Organization (2006) found that health workers contribute up to 80% to successful health development and one of the best ways to solve the health worker crisis is education, along with improved human resource management policies. and training. Health care workers are needed in health care services, so those who manage them need to take into account all their needs, wants and interests so that they can perform at their best. Exploring human resource development in Sarapian and Langkat districts.This type of research is qualitative research. Primary data are collected by in-depth interviews(Dept. Interview). Data from in-depth interviews with informants it was processed and analyzed using a content analysis approach. The types of health workers consist of Health Human Resources (HRD) in Langkat District, Salapian District, which are still dominated by medical personnel, including: 7% of dentists, 11.2% of general practitioners, 45% of midwives, 21.1% of nurses, while Community Health Workers are 5.6%, Environmental Health Workers are 2.8%, Pharmacy Staff are 4.2%, Health Nutrition Workers are 1.4%, and Medical Laboratory Technologists are 1.4%. HRH development is in accordance with needs development standards. Provision of training for HRH development isconfined to healthcare workers and its distribution is still uneven. Keywords: Health Human Resources, Development.